Planeta tierra. (Buenos Aires : Editorial Sigmar, 2001)
A general introduction to earth science in a question-and-answer format.
"Es una edicion Sigmar"--P. [4] of cover.
Includes index.
Keywords: Children's questions and answers -- Juvenile literature; Tierra -- Literauatura juvenil; Earth (Planet) -- Juvenile literature